RITUAL BEREQE SASAK UNTUK MELESTARIKAN NILAI SOSIAL RELIGIUS DAN JATI DIRI MASYARAKAT - Kamarudin Kamarudin (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2017)
This study explores values on traditional ceremony as public education in Sasak. The objective of ths study was to maintain social values, religious values, and self-esteem of the society for Indonesian integrity. This study used ethnographic design, exploring social values from the society. Data were collected using in-depth interview and observation. Data were analyzed inductively exploring taxonomy, domain and thematic analyses. The findings of the study were: bareqe ritual involved social values representing individual interactions to perform, care, solve problem in the society. Relegious values promoted praise to Allah, worship, and washing of sins in inner and physical. Self-esteem and integrity was represented as pride to involve in the ritual and maintain the values in the ritual devoted to the country.